The Influence of Tax Aggressiveness, Environmental Performance, Company Size on CSR Disclosure in Manufacturing Companies Listed on the IDX for the 2015-2021 Period - Nadia Astianata; Yudi Partama Putra (Penerbit Jurnal Indonesia, 2023)
his study aims to examine the effect of tax aggressiveness, environmental performance, company size and CSR disclosure in manufacturing companies for the 2015-2021 period. The population in this study are all manufacturing companies listed on the IDX in 2015-2021 and the samples used in this study were taken using a purposive sampling method. The samples in this study are annual reports and company financial reports starting from 2015-2021 consisting of 33 manufacturing companies that meet the criteria, and based on the research year period there are 231 samples. The data collection technique was through the website (www.idx.co.id) and the official website of each company that was sampled in the study. The data analysis used was descriptive statistical test, hypothesis testing and multiple linear analysis was processed using the SPSS 26.0 for Windows program. This study aims to determine how much influence tax aggressiveness, environmental performance and company size have on CSR disclosure in manufacturing companies listed on the IDX in 2015-2021. Based on the results of the research and discussion described in the previous chapter, the conclusions that can be drawn from this study are as follows: The results of this study indicate that tax aggressiveness has a significant effect on disclosure of corporate social responsibility (CSR), environmental performance has no significant effect on disclosure of corporate social responsibility (CSR), and company size has a significant effect on disclosure of corporate social responsibility (CSR).